INCREASING YIELD AND ITS QUALITY OF POTATO BY SPRAYING WITH NANOCHITOSAN LOADED WITH NPK, NETTEL AND GREEN TEA EXTRACTS - Z. R. J. AL- Malikshah; I. J. Abdulrasool (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to effect of spraying nano chitosan loaded with NPK and nettle leaf extracts and green tea on yield and its quality of potato for the spring and autumn seasons of 2021 in Al-Suwaira district of Wasit Governorate, It was conducted as a factorial experiment (5 × 5) within randomized complete block design with three replicates. The first factor included spraying with four concentrations of Nano chitosan loaded with NPK fertilizer at concentrations 0, 10. 15 and 20% in addition to chemical fertilization treatment, the second factor was spraying nettle leaf extract 25 and 35 gL-1 and green tea extract at 2 and 4 g.L-1, in addition to the control treatment, spraying with distilled water only. The results showed a significant superiority of the interaction between spraying with Nano chitosan loaded with NPK at a concentration of 15% and spraying green tea extract at a concentration of 4 g L-1 in producing the highest value for the leaf area of the plant amounted to 9973 and 9742 m 2 plant-1 and the highest yield per plant reached 1055.7 and 967.9 g.plant-1 for both seasons respectively, and the highest percentage of dry matter in tubers (24.31 and 22.77% for both seasons, respectively. The tuber content of the amino acid Arginine increased significantly. (324.1 and 318.8 mg 100g D.W.-1) and Glutamine (94.70 and 9453 mg 100g D.W.-1) for both seasons respectively.